2010
DOI: 10.1080/09515071003688165
|View full text |Cite
|
Sign up to set email alerts
|

Counsellor behaviours that predict therapeutic alliance: From the client's perspective

Abstract: The therapeutic alliance has been shown to be a robust predictor of counselling outcome. However, the specific counsellor behaviours that relate to the alliance have not been clearly and consistently identified, and prior attempts to identify these variables have not been typically based on client-derived conceptualizations of the alliance. A total of 79 adult counselling clients participated in a study examining the relationship between 15 client-identified counsellor behaviours and the strength of the therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…This study highlighted similarities to past research; that the interpersonal bond is imperative to the counselling process (Masdonati et al, 2009) and that specific verbal and non-verbal behaviours were identified as helping enhance the relationship when they were used appropriately (Duff and Bedi, 2010). For example, eye contact and having an open stance in session corroborate with Bedi and authors (2005) findings that facing the client squarely, openly and with eye contact is important to creating a positive bond.…”
Section: Discussionsupporting
confidence: 77%
“…This study highlighted similarities to past research; that the interpersonal bond is imperative to the counselling process (Masdonati et al, 2009) and that specific verbal and non-verbal behaviours were identified as helping enhance the relationship when they were used appropriately (Duff and Bedi, 2010). For example, eye contact and having an open stance in session corroborate with Bedi and authors (2005) findings that facing the client squarely, openly and with eye contact is important to creating a positive bond.…”
Section: Discussionsupporting
confidence: 77%
“…Content Analysis. A coding manual (Eskjaer & Helles, 2015;Krippendorff, 2012;Neuendorf, 2002) was developed for the study based upon previous content analysis of comforting messages (Bippus, 2001;Burleson, 1984Burleson, , 1985Burleson & Goldsmith, 1998;Burleson & Samter, 1985;Caplan & Turner, 2007;Jones & Burleson, 1997), counselor behavior (Bedi & Duff, 2014;Bedi & Mallinckrodt, 2006;Duff & Bedi, 2010;Fukkink & Hermanns, 2007, 2009Nieuwboer, Fukkink, & Hermanns, 2014;Williams et al, 2009), social support behavior (Cutrona & Russell, 1990;Cutrona & Suhr, 1992;Fukkink, 2011), and helper responses (Mishara & 1997; Mishara et al, 2007a,b), adapted to the specificity of this particular context. Three master's degree students and two counseling employees, who were blind to the impact scores, were trained by the first author to rate the session transcripts (522 sessions/7,657 messages).…”
Section: Data Sets and Instrumentsmentioning
confidence: 99%
“…Research has indicated that alliances are rated more highly by clients when positive counsellor qualities are in evidence, for example, Duff and Bedi (2010) found that the enactment of warm human qualities accounted for 62% of the variance in alliance scores.…”
Section: Being Real Helps the Alliancementioning
confidence: 99%